Relations Between the Characteristics of Granular Column Collapses and Resultant High‐Frequency Seismic Signals. Issue 12 (23rd December 2019) - Farin, Maxime; Mangeney, Anne; de Rosny, Julien; Toussaint, Renaud; Trinh, Phuong‐Thu
Abstract : Deducing relations between the dynamic characteristics of landslides and rockfalls and the resultant high‐frequency (>1 Hz) seismic signal is challenging. To investigate relations that can be tested in the field, we conducted laboratory experiments of 3‐D granular column collapse on a rough inclined thin plate, for a large set of column masses, aspect ratios, particle diameters, and slope angles. The dynamics of the granular flows were recorded using a high‐speed camera, and the generated seismic signal was measured using piezoelectric accelerometers. Empirical scaling laws are established between the characteristics of the granular flows and deposits and that of the generated seismic signals. The radiated seismic energy scales with particle diameter as d 3, column mass as M and aspect ratio as a 1.1 . The increase of the radiated seismic energy as slope angle increases correlates with a similar increase in particle agitation. Based on our experimental results, we revisit scaling laws reported in the field and discuss their possible physical origin. The discrepancy between field and experimental observations can be explained by the complex influence of the substrate on seismic signal and the difference of flow initiation in both cases. However, our empirical scaling laws allow us to determine which flow parameters could be inferred from a given seismic characteristic in the field. In particular, by assuming the flow average speed is known, we show that we can retrieve parameters d, M, and a within a factor of two from the seismic signal. Key Points: We conduct granular column collapse experiments with various initial conditions and seismic measurements Empirical scaling laws are established between the dynamics and seismic parameters The increase of radiated seismic energy with slope angle matches with the increase in particle agitation